(3bUjOI aj GdOhdI GdYKeGfjIs - (3YHO GdLdjd Hf jGSjf Hf EHQGgje Hf Wg Hf Ndjd GdWHGWHGFj GdMSfj GdHUQj, YHO GdLdjd jGSjf,J (B1270 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CeO GdOhdI GdYKeGfjI HHSWI GdJCjjO HTQi HYR bO CVGA eNdO TedJ Hg GdCaQGM cd ehMO s
(3BNQgG (B:s
(3hdGRGd ebGe ehdGfG bQjf GdYR Bejf Bejf dG CQVi HhGMOI MJi CVja EdjgG Cda BejfG s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B276s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B327 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs